Warm conveyor belt activity over the Pacific: modulation by the Madden–Julian Oscillation and impact on tropical–extratropical teleconnections - J. F. Quinting; C. M. Grams; E. K.-M. Chang; S. Pfahl; H. Wernli (Weather and Climate Dynamics, 2024)
Research in the last few decades has revealed that rapidly ascending airstreams in extratropical cyclones – so-called warm conveyor belts (WCBs) – play an important role in extratropical atmospheric dynamics. However on the subseasonal timescale, the modulation of their occurrence frequency, henceforth referred to as WCB activity, has so far received little attention. Also, it is not yet clear whether WCB activity may affect tropospheric teleconnection patterns, which constitute a source of predictability on this subseasonal timescale. Using reanalysis data, this study analyzes the modulation of WCB activity by the Madden–Julian Oscillation (MJO). A key finding is that WCB activity increases significantly over the western North Pacific when the convection of the MJO is located over the Indian Ocean. This increased WCB activity, which is stronger during La Niña conditions, is related to enhanced poleward moisture fluxes driven by the circulation of subtropical Rossby gyres associated with the MJO. In contrast, when the convection of the MJO is located over the western North Pacific, WCB activity increases significantly over the eastern North Pacific. This increase stems from a southward shift and eastward extension of the North Pacific jet stream. However, while these mean increases are significant, individual MJO events exhibit substantial variability, with some events even exhibiting anomalously low WCB activity. Individual events of the same MJO phase with anomalously low WCB activity over the North Pacific tend to be followed by the known canonical teleconnection patterns in the Atlantic–European region; i.e., the occurrence frequency of the positive phase of the North Atlantic Oscillation (NAO) is enhanced when convection of the MJO is located over the Indian Ocean and similarly for the negative phase of the NAO when MJO convection is over the western North Pacific. However, the canonical teleconnection patterns are modified when individual events of the same MJO phase are accompanied by anomalously high WCB activity over the North Pacific. In particular, the link between MJO and the negative phase of the NAO weakens considerably. Reanalysis data and experiments with an idealized general circulation model reveal that this is related to anomalous ridge building over western North America favored by enhanced WCB activity. Overall, our study highlights the potential role of WCBs in shaping tropical–extratropical teleconnection patterns and underlines the importance of representing them adequately in numerical weather prediction models in order to fully exploit the sources of predictability emerging from the tropics.